Obtaining optic disc center and pixel region by automatic thresholding methods on morphologically processed fundus images. Issue 2 (February 2015) - Marin, Diego; Gegundez-Arias, Manuel E.; Suero, Angel; Bravo, Jose M.
<x xml:space="preserve">Abstract</x> Graphical abstract